Risk management committee and firm performance: The moderating effect of political connection - Afrizal, Faris; Oktavendi, Tri Wahyu; Irawan, Dwi (Universitas Muhammadiyah Yogyakarta, Indonesia, 2025)
Research aims: This study seeks to prove empirical evidence regarding the moderating effect of political connection to risk committee and firm performance relationship.Design/Methodology/Approach: The method used in this research uses a quantitative approach. The data used is financial companies registered on the Indonesian Stock Exchange (IDX) in the 2019 – 2021 period. The data used and meets the criteria is 129 data.Research findings: The research results show that the size of the risk management committee has an influence on firm performance. The large number of risk management committee members helps companies assess potential risks early. Political connections weaken the relationship between the risk management committee and firm performance. Theoretical contribution/ Originality: The originality of this research is based on the moderating results of political connections which provide a weakening effect compared to previous studies. Practitioner/Policy implications: For practitioners and companies, they can consider it in decision making before having a board of directors join politicsResearch limitations/Implications: Limitation of this research is research scope just in financial sector and only risk committee size used in this research.